Tantangan dan Peluang Penyandang Disabilitas Fisik di Kota Bandung dalam Memperoleh Pekerjaan di Masa Covid-19 - Didan Akbar Zaelani; Divo Sangrila Yusuf; Ade Yunita Mafruhat; Wiedy Yang Essa (Jurnal Sosial Humaniora, 2022)
This article seeks to identify the barriers to employment, as well as theopportunities and rights fulfilment for those with physical impairments in theCity of Bandung during the Covid-19 period. It's intriguing to talk about thechances and difficulties people have; they worry about obtaining work in theCovid-19 era. The descriptive qualitative approach of data analysis employedin this study refers to the events that occurred and data collection methodsusing interviews, observations, and documentation. By interviewing 22people with physical disabilities in the city of Bandung. The results of thearticle show that labor absorption and policies to fulfil the right to work forpeople with physical disabilities in Bandung City have not been optimal, withsix challenges faced, including limited information related to employment andtraining, low self-confidence, negative stigma, educational background, jobopportunities and skills. On the other hand, there are four opportunities forpeople with physical disabilities in the city of Bandung to find work, includingthe government monitoring the absorption of workers with disabilities, theavailability of job seekers applications, the ability to work for people withphysical disabilities and the implementation of training programs.